2016
DOI: 10.1007/s40843-016-5057-8
|View full text |Cite
|
Sign up to set email alerts
|

Hollow MO x -RuO2 (M = Co, Cu, Fe, Ni, CuNi) nanostructures as highly efficient electrodes for supercapacitors

Abstract: Engineering the internal structure and chemical composition of nanomaterials in a cost-effective way has been challenging, especially for enhancing their performance for a given application. Herein, we report a general strategy to fabricate hollow nanostructures of ruthenium-based binary or ternary oxides via a galvanic replacement process together with a subsequent thermal treatment. In particular, the as-prepared NiO-RuO2 hollow nanostructures loaded on carbon nanotubes (hNiO-RuO2/CNT) with RuO2 mass ratio a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Owing to the easy‐to‐manipulate microstructure and delimited local voids, researchers recently have demonstrated that elaborated hollow nano/microstructures exhibit superior performance as the primary materials in a variety of emerging research fields, such as catalysis, lithium‐ion batteries (LIBs), supercapacitors, proton‐exchange‐membrane fuel cells (PEMFCs), chemical sensors, and biomedicine . Along with tremendous progress on microstructural characterizations and basic growth mechanism of nanocrystals, hollow nanomaterials become one of the hot spots in the modern research of nanoscience, particularly focusing on the development of synthetic methodologies and structure‐correlated properties …”
Section: Introductionmentioning
confidence: 99%
“…Owing to the easy‐to‐manipulate microstructure and delimited local voids, researchers recently have demonstrated that elaborated hollow nano/microstructures exhibit superior performance as the primary materials in a variety of emerging research fields, such as catalysis, lithium‐ion batteries (LIBs), supercapacitors, proton‐exchange‐membrane fuel cells (PEMFCs), chemical sensors, and biomedicine . Along with tremendous progress on microstructural characterizations and basic growth mechanism of nanocrystals, hollow nanomaterials become one of the hot spots in the modern research of nanoscience, particularly focusing on the development of synthetic methodologies and structure‐correlated properties …”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that, in addition to hollow binary nanoboxes and oxide nanostructures, galvanic replacement could also be applied to generate hollow nanotubes [329,350,351], nanocages [352][353][354], multiple-walled nanoshell [355] and so on. Most recently, Yang and co-workers [356] reported the galvanic replacement of Ru and a set of transition metals such as Co, Cu, Fe and Ni to fabricate hollow nanostructures. Moreover, after a simple thermal treatment in air, the bimetallic structures can be in-situ transformed into the hollow metal oxides structures without changing their symmetry.…”
Section: Replacement Reaction For Oxidesmentioning
confidence: 99%
“…As a new energy storage approach, SCs combine the advantages of high energy density of rechargeable batteries and high power density of dielectric capacitors [19][20][21][22][23][24][25][26][27][28][29]. SCs have been regarded as highly important candidates for energy storage devices because of their fast charging-discharging capability, long cycle stability (>10 5 cycles), high power density (>10 kW kg −1 ), low cost, environment-friendly nature, low maintenance, and safe operation [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. In certain fields, SCs can partly or fully replace traditional batteries.…”
Section: Introductionmentioning
confidence: 99%